Persepsi Masyarakat Terhadap Fenomena Kekerasan Dalam Rumah Tangga di Desa Kalangan Baturetno Banguntapan Bantul - Azizah, Qoirina Nur; Kurnia, Heri (Academy of Social Science and Global Citizenship Journal, 2022)
This study aims to determine the public's perception of the phenomenon of domestic violence cases, determine the factors that cause domestic violence, the forms of violence experienced by victims, the psychological impact of women as victims of violence, and recovery efforts for victims of violence. The researcher took the location in Kalangan Village, Banturetno Village, Banguntapan District, Bantul Regency. The subject of this research is the community. The type of research used in this research is qualitative research. The design used in this study is descriptive which aims to describe the tendency of people's perceptions of domestic violence. The sampling technique in this study was purposive proportional random sampling. Data collection methods used by researchers are interviews, questionnaires (questionnaire) and documentation. The results of the study show that the people of Kalangan Baturetno Banguntapan Bantul Village still think that the phenomenon of domestic violence is a shame that must be hidden, because they feel ashamed of not being able to keep their families in harmony. The main causal factors in the phenomenon of domestic violence cases in Kalangan Village are the main problems of infidelity, differences of opinion and economic problems. The forms of violence experienced by victims of domestic violence are physical violence (slapped, grabbed, etc.), psychological violence (swearing, threats), sexual violence. Usually victims who experience domestic violence will experience trauma, victims feel anxious, scared, depressed, often daydream, moody, cry easily, have trouble sleeping, and have nightmares.